Quality control in bearing manufacturing company using statistical proces control (SPC) - Panirchelvan, Ramanathan (2009)
Statistical process control(SPC) is an important tool used widely at manufacturing field to monitor the overall operation. SPC can be applied to all kind of manufacturing operations. The significant application of the SPC analysis elements to the operation will make the process more reliable and stable. For the case study, bearing manufacturing process were selected. Bearing is one of important part in mechanical devices. A complete bearing consist of outer ring, steel ball, cage, metallic shield and inner ring. The dimensions of the bearing components are must control tight to its tolerance to ensure the bearing fit to its clearance. To ensure the process is under the production control statistical process control (SPC) methods are being used. To converge the study on SPC application on the bearing manufacturing processes, a visit to SKF Bearing Industries (Malaysia) Sdn. Bhd. has been made. The case study was done on bearing product number 6206-2Z. The bearings outer ring manufacturing processes were take into consideration. Each processes of the outer ring making were observed carefully. The quality control (QC) data were obtained from SKF and further analysis on the data was done manually and by using MINITAB software. The analyzed data were compared and the root problems and errors were identified. The problems are further discussed and some recommendations were made to make the process more efficient. In the bearing industry, bearings outer ring making operation is on of the critical process. Significant differences in dimension and deviation from the parts tolerance will make the bearing produced is rejected or categories as low quality bearing. A class 1 bearing will have tight clearance. Statistical process control will monitor the processes and magnifies the small deviations of the process from the actual control limits. Thus, the manufacturing processes can be controlled directly and good bearing which meets all the specifications can be produced.